Prediction and Rationalization of Different Photochemical Behaviors of mer - and fac -Isomers of [Ru(pyridyltriazole) 3 ] 2 - Scattergood, Paul A; Elliott, Paul I P (Inorganic chemistry, 2024)
Facial and meridional isomerism of metal complexes is known to result in fundamental differences in photophysical properties. One may also envisage differences in their photochemical reactivity and therefore predict different outcomes of their light-triggered transformations. The - and -isomers of the complex [Ru(pytz) ] ( - & - , pytz = 1-benzyl-4-(pyrid-2-yl)-1,2,3-triazole) were separated and isolated. - undergoes a predicted pytz photodechelation process in acetonitrile to yield -[Ru(κ -pytz) (κ -pytz)(NCMe)] ( ) whereas unfavorable interligand steric interactions are predicted to, and indeed do prevent comparable photoreactivity for - . Reversible photoisomerization of - and - is also observed, however. The differences in photochemical reactivity of the two isomers can be rationalized based on structural programming of the preferential accessibility of particular MC excited states due to differences in their interligand steric interactions. Here we present an initial predictive thought experiment, subsequent experimental verification, and computational rationalization of the differences in photochemical reactivity of these two isomeric complexes.